Cloud computing : challenges, limitations and R&D solutions - Mahmood, Zaigham (Computer Communications and Networks, 2014)
This important text/reference reviews the challenging issues that present barriers to greater implementation of the cloud computing paradigm, together with the latest research into developing potential solutions. Exploring the strengths and vulnerabilities of cloud provision and cloud environments, Cloud Computing: Challenges, Limitations and R&D Solutions provides case studies from a diverse selection of researchers and practitioners of international repute. The implications of emerging cloud technologies are also analyzed from the perspective of consumers. Topics and features: Presents a focus on the most important issues and limitations of cloud computing, covering cloud security and architecture, QoS and SLAs Discusses a methodology for cloud security management, and proposes a framework for secure data storage and identity management in the cloud Introduces a simulation tool for energy-aware cloud environments, and an efficient congestion control system for data center networks Examines the issues of energy-aware VM consolidation in the IaaS provision, and software-defined networking for cloud related applications Reviews current trends and suggests future developments in virtualization, cloud security, QoS data warehouses, cloud federation approaches, and DBaaS provision Predicts how the next generation of utility computing infrastructures will be designed The insights provided by this practically-focused collection will be of great benefit to students, lecturers and researchers interested in the state of the art of cloud computing. Software developers, infrastructure managers, and other cloud practitioners will also find the book to be a helpful guide.